2016
DOI: 10.12659/msm.901686
|View full text |Cite
|
Sign up to set email alerts
|

Suprapedicular Foraminal Endoscopic Approach to Lumbar Lateral Recess Decompression Surgery to Treat Degenerative Lumbar Spinal Stenosis

Abstract: BackgroundTo discuss the strategy of suprapedicular foraminal endoscopic approach to lumbar lateral recess decompression and evaluate the safety and effectiveness of this strategy.Material/MethodsComplete clinical information of 52 cases of lumbar lateral recess decompression with therapy of suprapedicular foraminal endoscopic approach were analyzed during the period from February 2010 to April 2014 in the Third Hospital of Hebei. All patients were followed up for 24 months, and VAS, JOA, ODI, and LRD were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Kambin et al [ 13 ] acquired satisfactory results by using the mildest decompression, but cases of severe intervertebral disk narrowing and bony LRS were excluded. Li et al [ 14 ] and Wang et al [ 15 ] reported good clinical results by more aggressive dorsal and caudal bony structure removal. However, the power of persuasion was weakened by mixing or not clearly excluding the cases with concomitant disk herniation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kambin et al [ 13 ] acquired satisfactory results by using the mildest decompression, but cases of severe intervertebral disk narrowing and bony LRS were excluded. Li et al [ 14 ] and Wang et al [ 15 ] reported good clinical results by more aggressive dorsal and caudal bony structure removal. However, the power of persuasion was weakened by mixing or not clearly excluding the cases with concomitant disk herniation.…”
Section: Discussionmentioning
confidence: 99%
“…For ventral decompression, removal of fibrotic bulging annulus, contained disk, posterolateral marginal osteophytosis, or even removal of endplate and posterior part of vertebral body have been reported [ 13 , 20 , 21 ]. In addition, caudal pedicle has been reported to be partially resected for more caudal decompression [ 15 ]. But the necessary range of decompression has not been clearly documented in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of patients who received decompression of the lumbar lateral recess using a suprapedicular foraminal endoscopic approach, the combined excellent and good rate was 84.62%, and the technique was shown to be safe and effective with satisfactory outcomes, particularly for elderly patients with complicated underlying diseases. 10 The authors commented, however, that there is more blood loss when treating lateral recess stenosis using transforaminal endoscopic surgery. 10 A study of microscope-guided treatment of lumbar spinal stenosis disease through the intervertebral foramen reported that the operation time for this type of surgery was short, haemorrhage was minimal, and operative and postoperative complications were slightly more than those of conventional surgery.…”
Section: Discussionmentioning
confidence: 99%
“…10 The authors commented, however, that there is more blood loss when treating lateral recess stenosis using transforaminal endoscopic surgery. 10 A study of microscope-guided treatment of lumbar spinal stenosis disease through the intervertebral foramen reported that the operation time for this type of surgery was short, haemorrhage was minimal, and operative and postoperative complications were slightly more than those of conventional surgery. 3 Thus, the authors concluded that this approach was safe and effective for lumbar spinal stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…All these causes pressurize the nerve root which leads to the disease. The purpose of intervention in this disease is to decrease the pressure and tension applied on the nerve by removing the source of pressure [6][7][8][9][10][11][12]. The percutaneous foraminotomy introduced in this case report is a newly developed minimally invasive device that reduces pressure on the nerve root as well as the blood vessels in the neural canal.…”
Section: Discussionmentioning
confidence: 99%